PENGARUH PEMBELAJARAN MATEMATIKA BERBASIS PROYEK TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS X SMAN 1 PEGAJAHAN - Yuka Fadhilla; Lisa Dwi Afri (Universitas Bhinneka PGRI, 2024)
This study aims to examine the impact of Project-Based Learning (PjBL) on the problem-solving abilities of tenth-grade students at SMA Negeri 1 Pegajahan within the context of the Merdeka Curriculum. The research employs a quantitative method with a quasi-experimental approach, utilizing a Pretest-Posttest Only One Group Design. The population includes all tenth-grade students, with samples selected using Cluster Random Sampling techniques. Data were collected through pretests and posttests and analyzed using descriptive and inferential statistical tests, including normality tests, homogeneity tests, and the Paired Sample t-Test. The results indicate a significant improvement in students' problem-solving abilities following the implementation of PjBL. The t-test results demonstrate a positive effect of PjBL on students' problem-solving skills. Based on these findings, it is concluded that PjBL is an effective teaching method for enhancing students' mathematical problem-solving abilities. This study provides valuable contributions to the development of more innovative and relevant teaching methods, particularly in supporting the implementation of the Merdeka Curriculum in Indonesia.